Atividade antibacteriana e antibiofilme de Lactobacillus paracasei isolados de grãos de kefir contra enterobactérias resistentes - Magalhães, Edrine Vasconcelos Farias (2024)
The increasing antimicrobial resistance of enterobacteriaceae poses a significant challenge in healthcare, becoming a global concern due to the limited availability of effective therapeutic options. In this context, probiotics isolated from various sources, such as strains of the Lactobacillus genus, have emerged as a promising approach to combat resistant infections. This study investigated the antibacterial and antibiofilm activity of L. paracasei strains (Lpk 01) previously isolated from kefir grains against strains of Escherichia coli (C22, C27, C55, and ATCC 11303) and Klebsiella spp. (C17, C21, C28, and ATCC 700603). Initially, the antibiotic sensitivity of Lpk 01 was established through broth microdilution according to BrCAST standards. Subsequently, the antagonistic activity of the probiotic strain against the enteropathogens was evaluated using the Spot Overlay technique. The supernatant of Lpk 01 (Lpk-cf) was then prepared and tested for antimicrobial activity using the microdilution test. Finally, the effect of non-neutralized Lpk-cf on pre-formed (24h) biofilms was tested. Lpk 01 showed sensitivity to most of the antimicrobials tested. Furthermore, the results demonstrate potent antagonism of Lpk 01 against enterobacterial strains (R>6mm), with the inhibitory capacity varying according to the medium's pH. This effect was confirmed with the microdilution test, in which the non-neutralized Lpk-cf inhibited planktonic growth, showing an antimicrobial effect ranging from 20 to 50% of Lpk-cf. Statistically significant differences compared to the control were observed in all studied strains, and all Lpk-cf percentages were tested without an apparent dose-response relationship, with an average reduction of 50% of biomass. Thus, the results indicate that Lpk 01 has promising antibacterial and antibiofilm potential, suggesting this probiotic strain is a therapeutic alternative against enteropathogens.